Visual learning interactive infographic for civil procedure students in law schools in Malaysia / Azhani Arshad ... [et al.] - Arshad, Azhani; Mat Ali, Syuhaeda Aeni; Maso’od, Ummi Hani’; Hassan, Che Audah (Universiti Teknologi MARA, Kedah, 2023)
In Malaysia, one of the core courses in the body of knowledge for law programs in MQA Programme Standards is the procedural course, Civil Procedure. This course offers the students the knowledge and practical skill in applying and implementing procedural law in conducting civil action at the court. This course is considered ‘dry’ in nature, which the students felt and showed difficulties visualising the process. Thus, to overcome the above, it is essential to figure out and implement a proper delivery and learning approach using a beneficial and convenient tool by virtual learning techniques such as mind/ process mapping and flowcharts. Hence, the authors develop an interactive infographic that enables end-users to visualise the court proceeding. The interactive infographic aims to present information in a way that suits the interest of the students, to enhance the law students’ understanding of law subjects and promote effective teaching and learning by integrating mind/process mapping and flowchart techniques. It is a user-friendly interface that presents information in a way that is visually appealing and easy to understand, which makes it easy, efficient and enjoyable to operate as it is designed by using, among others, explicit language, patterns in layout and design, colour, contrast and texture in features, and legibility in typography. With this kind of delivery and learning approach, the students can improve their understanding of the core substance with the ability to analyse and apply it on a summative examination at the end of a course and for life-long learning.